Lysozyme gene insertion in striped catfish Pangasianodon hypophthalmus (Sauvage, 1878) to generate desease resistence breeds line - Wartono Hadie; Sularto Sularto; Lies Emmawati Hadie; Angela Mariana Lusiastuti; Alimuddin Alimuddin; Evi Tahapari; Huria Marnis (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2015)
Bacterial disease in catfish has many detrimental to farmers, especially in the larvae stadium in the hatchery up to ready size of stocking seed. Therefore we need technology that can produce disease resistant of catfish. In that regard, one of the antimicrobial enzyme namely lysozyme which plays an important role in the maternal immunity can be introduced into the catfish genome. This study aimed to evaluate the success of the lysozyme gene insertion into the genome of striped catfish to generate maternal disease resistance. Gene transfer method was done by using electroporation on striped catfish spermatozoa. Lysozyme plasmid electroporation performed with a dose 100^g ml-1 and 125V.cm-1, pulse length 30 milliseconds with a pulse interval 0.1 milliseconds and pulse number 5 times. Electroporated spermatozoa were used to fertilize the egg. Lysozyme gene insertion success was indicated by tests performed on embryogenesis, larval, and seed stage. The test results at both DNA and RNA level showed a positive result. Individual that brings the lysozyme gene will be used as a candidate for breed line maternal immune as other ways to formation of resistant disease varieties. Abstrak Serangan penyakit bakterial pada ikan patin telah banyak merugikan para pembudi daya ikan patin terutama pada seg-men perbenihan hingga ukuran siap tebar. Oleh karena itu diperlukan teknologi yang mampu menghasilkan ikan patin yang tahan penyakit. Berkaitan dengan hal itu, salah satu enzim antimikroba yaitu lisozim yang memainkan peranan penting dalam imunitas bawaan dapat diintroduksikan ke dalam genom ikan. Penelitian ini bertujuan untuk mengevalu-asi keberhasilan insersi gen lisozim ke dalam genom ikan patin siam sebagai galur ikan patin tahan penyakit. Transfer gen dilakukan dengan menggunakan teknik elektroporasi pada spermatozoa ikan patin siam. Elektroporasi dilakukan dengan konstruksi gen lisozim berupa plasmid DNA dosis 100 ^g.ml-1 dengan voltase 125 V. cm-1, panjang kejutan 30 milidetik dengan interval kejutan 0.1 milidetik dan jumlah kejutan lima kali. Spermatozoa hasil elektroporasi digunakan untuk membuahi telur. Pengujian keberhasilan insersi gen lisozim dilakukan pada tahap embrio larva, dan pada benih. Hasil pengujian, baik pada tingkat DNA maupun pada tingkat RNA dari sampel spermatozoa dan larva (whole cell), memperlihatkan hasil yang positif. Individu ikan patin yang membawa gen lisozim dan telah terintegrasi ke dalam ge-nomnya akan digunakan sebagai kandidat dalam pembentukan galur ikan patin tahan penyakit.